If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(2x + -1) = 19 Reorder the terms: 4 + -1(-1 + 2x) = 19 4 + (-1 * -1 + 2x * -1) = 19 4 + (1 + -2x) = 19 Combine like terms: 4 + 1 = 5 5 + -2x = 19 Solving 5 + -2x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 19 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 19 + -5 -2x = 19 + -5 Combine like terms: 19 + -5 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| x^2-8x+16=54 | | 6x-6=2x-18 | | 10=-3k-2k | | 3x+3+5x-7=28 | | 0,5z+6=z-1 | | 3x+1=7x+3 | | (6+u)(4u+5)=0 | | 5k-k=48 | | 4x(x-1)=(2x+5)(2x-5)+1 | | 3(f+2)=-15 | | 19=7+3y | | -15=n-3-5n | | -9m^2+11m-2+4m^2-8m+7= | | 7p+2p=99 | | 2(3t-5)=3t+15 | | -2a-6a=16 | | x(x+2)-13=(x-3)(x+3) | | x+3x+5x+2x+7= | | 56n^2+63=0 | | 2g+1=5 | | 3(2x-5y+4)= | | 6y+x=15 | | 4+(3)n=13 | | 11x=8x+27 | | 11x=6x+35 | | 7x=2x+45 | | 3(m-4)-(m+2)=0 | | 6(4x-7)=12 | | 6x^2+12x+4=0 | | 2(7x+2)=2x | | 3+3m+1=2m+4+m | | 7(8x-5)=21 |